Experimental Investigation on Nonlinear Flow Anisotropy Behavior in Fracture Media. (24th June 2019) - Zhu, Chun; Xu, Xiaoding; Wang, Xiuting; Xiong, Feng; Tao, Zhigang; Lin, Yun; Chen, Jing
Abstract : A series of flow experiments were performed on matched fractures to study the problem of non-Darcy flow in fractured media. Five rock fractures of different roughness were generated using indirect tensile tests, and their surface topographies were measured using a stereo topometric scanning system. The fracture was assumed to be a self-affine surface, and its roughness and anisotropy were quantified by the fractal dimension. According to the flow tortuosity effect, the nonlinear flow was characterized by hydraulic tortuosity and surface tortuosity power law relationships based on Forchheimer's law. Fracture seepage experiments conducted with two injection directions (0° and 90°) showed that Forchheimer's law described the nonlinear flow well. Both the proposed model and Chen's double-parameter model gave similar results to the experiment, but the match was closer with the proposed model. On this basis, a new formula for the critical Reynolds number is proposed, which serves to distinguish linear flow and Forchheimer flow.